(untitled) - Gut, Allan (New York, 2005)
This textbook provides a purely mathematical discipline, probability theory is an intimate companion of statistics. The book starts with the basic tools, and goes on to chapters on inequalities, characteristic functions, convergence, followed by the three main subjects, the law of large numbers, the central limit theorem, and the law of the iterated logarithm. After a discussion of generalizations and extensions, the book concludes with an extensive chapter on martingales.
Keywords: Probabilities,Distribution (Probability theory),Probabilistic number theory,Xác suất,Phân bổ (lý thuyết xác suất),Lý thuyết số xác suất